VP1 protein of Foot-and-mouth disease virus (FMDV) impairs baculovirus surface display - Peralta, Andrea Verónica (2013)
The Foot-and-mouth disease virus (FMDV) causes important economical losses in livestock farming. In order to develop a novel subunit vaccine against FMDV, we constructed recombinant baculoviruses that display the protein VP1 of FMDV on their surface, with either polar (fused to gp64) or nonpolar (fused to anchor membrane from VSV-G protein) distribution. Insect cells infected with the different recombinant baculoviruses expressed VP1 fusion protein to high levels. However, the recombinant VP1 protein was not carried by budded virions. Subcellular localization of VP1 revealed that the trafficking of the fusion protein to the cell plasma membrane was impaired. Our results suggest that VP1 contains cryptic domains that interfere with protein secretion and subsequent incorporation into budded baculoviruses.